(untitled) (Biodiversitas Journal of Biological Diversity, 2007)
Jabon Mekar village is well-known as the central of fruit supplayer at subdistrict of Parung. Many kinds of fruit were planted and developed in this area. Durian ‘lai-mas’ or durian jabon’s cultivar is the superior product of fruit. However it was estimated as a buffer zone of Jakarta and subject of the urban development. Due to the increasing number of the urbant development in Jakarta, it is concerned that this will have an effect to the function of home-garden.The aim of the research is to study the potential riches and fruit plant diversity at homegarden of community in the village of Jabon Mekar. The methods used for vegetation analysis were the quadratic method. The result of the research found 57 species of fruit plants from 41 genus, 23 families and 30 local cultivars. From all fruit of plants, there are 7 species as the main compositer of the community at home-garden i.e. Musa sp., Durio zibethinus, Nephelium lappaceum, Cocos nucifera, Artocarpus heterophyllus, Sandoricum koetjape, Carica papaya. It was found also that the diversity of plant species at home-garden was at the high level. While all fruit of plant species found a tendency SDR value under 50%, means that none of the plant species dominant toward other fruit of plants species. © 2007 Jurusan Biologi FMIPA UNS Surakarta Key words: Jabon Mekar, home-garden, fruit plant, riches, diversity